Migrants and Disaster Subcultures in the Late Anthropocene: An Ecocritical Reading of Octavia Butler’s Parable Novels - Federmayer, Éva (Hungarian Journal of English and American Studies, 2020)
Affected by a shocking concatenation of ecological, economic, and political disasters, black, white, and multiracial characters in Octavia Butler’s Parable of the Sower (1993) and Parable of the Talents (1998) seek to cope with apparently insurmountable difficulties. These Afrofuturist Parable novels render a disintegrating US society in the 2020s-2090s, which is torn by internal and external chaos: it shows visible signs of pandemonium involving the crisis of individual, communal, and ecological survival. This ecocritical reading seeks to explore how Butler’s novels make up the fictional tapestry of an evolving human risk narrative whose anthropogenic effects on the planet might threaten an “ecological holocaust” (Charles Brown) unless fundamental green changes spur radically alternative modes of thinking and living. Throughout this paper, I am interested in how Butler’s texts address and construct the interaction of the human and the non-human world to create a storyworld in which distinct characters operate not only according to the logic of the narrative in their local places and (semi)private/communal spaces, but also as distinct configurations of the Anthropocene, that is, as agents of a larger story of humans. (EF)